PENGARUH KONSELING MENYUSUI TERHADAP SIKAP MENYUSUI IBU POSTPARTUM YANG DIRAWAT - Sri Mulyani (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2016)
Abstract: Breastfeeding is important for mothers giving birth. Breastfeeding counseling is one of the efforts for the success of breastfeeding. The purpose of this study was to determine the effect of breastfeeding counseling on maternal breastfeeding attitudes treated. Design research is a quasi-experimental design with post-test-only approach to non equivalent control group. Total sample of 60 people were taken using a technique nonprobability sampling (non-random sample) with consecutive sampling method. Results showed no effect of breastfeeding counseling on breastfeeding maternal attitude (p value = 0.02). Age, education, parity, ethnicity, breastfeeding experience, the experience gets the information and family support is not related to breastfeeding attitudes. The role of health workers as breastfeeding counselors need to be optimized for successful breastfeeding maternal treated. Keywords: breastfeeding counseling, breastfeeding attitudes, maternal